English - Pradeliana, Dewa Satrio; Margaretha, Yolla (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 2 Tahun 2024DO - 10.24843/MATRIK:JMBK.2024.v18.i02.p04, 2024)
This study explores the influence of personal and organizational characteristics on the motivation of successors in family business succession in Indonesia. Through a survey involving 30 respondents from West Java, data were analyzed using NVivo software. Findings indicate that age, gender, and business scale influence successor motivation, especially when succession plans are in place. The research highlights the importance of mature succession planning as a key to family business success. These findings can support the development of more effective policies and improvements in succession process management. Limitations of the study include questions that do not consider the business sector comprehensively and the need for a more varied sample. Future research can enrich this model and address these limitations to deepen understanding of family business succession.   Keyword : family business succession, personal characteristics, organizational characteristics, motivation